THE EFFECT OF PRODUCTION FACTOR OF ONIONS PRODUCTION - Muhammad Thamrin; Sasmita Siregar; Nopraidy Rambe (JASc (Journal of Agribusiness Sciences), 2017)
The aim of the study was to find out  the effect of  land area, seeds, fertilizer, pesticide and workers on the production of onions, to know the elasticity of production factor of onions cultivation and  appropriateness of onions cultivation. The result of this research can be concluded that simultaneously (serempak) onions production were influenced by wide of  land area, seeds, fertilizer, pesticide and workers by 96%. The statistical test results obtained by the value of Multiple R of 0.98,  it meant there was a close relationship between land area, seeds, fertilizer, pesticide and workers of onions production by 98%. Partially, the variable of land area, seeds and pesticides have significant effect on onions production with 95% confidence level, while the variable of fertilizer and workers did not have effect significantly of onions production at 95% confidence level, appropriateness of onions cultivation based on R / C and B / C Ratio was feasible to cultivate.Keywords: Production Factor, Elasticity, Appropriateness